2013
DOI: 10.1177/1049909113490068
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Adaptation of the Transtheoretical Model to Narratives of Bereaved Family Members in the Bereavement Life Review

Abstract: This study aimed to examine the possibility of adaptation of the transtheoretical model (TTM) to narratives from the Bereavement Life Review. Narratives from 19 bereaved family members were recorded, transcribed into sentences, and allocated into stages based on the TTM criteria. Those who lived in fantasy were allocated to the precontemplation stage and who recognized the patient's death but could not adjust to the death were allocated to the contemplation stage. Those who understood the need for changes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Within the 18 included studies providing qualitative data, we found 2 reports[912] with qualitative evaluations from RCTs,[815] 15 other studies,[111720222526272829303132333435] and 1 qualitative evaluation of transcripts of dignity therapy. [36] In addition to the reports from RCTs, three studies followed a mixed methods approach.…”
Section: Resultsmentioning
confidence: 99%
“…Within the 18 included studies providing qualitative data, we found 2 reports[912] with qualitative evaluations from RCTs,[815] 15 other studies,[111720222526272829303132333435] and 1 qualitative evaluation of transcripts of dignity therapy. [36] In addition to the reports from RCTs, three studies followed a mixed methods approach.…”
Section: Resultsmentioning
confidence: 99%